Phase-map fringe pixel tracing for height computation - Retnasamy, Vithyacharan; Poopalan, Prabakaran, Assoc. Prof. Dr. (Institute of Electrical and Electronics of Engineering (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/